The ecosystem services concept as a tool for public participation in management of Poland’s Natura 2000 network - Mączka, Krzysztof; Chmielewski, Piotr; Jeran, Agnieszka; Matczak, Piotr; van Riper, Carena J. (Elsevier, 2019)
This paper examined how the ecosystem services (ES) concept was employed as a tool for stakeholders from different social and professional worlds to deliberate about the management of Natura 2000 areas in Poland. Drawing from Framing Theory and discourse analysis, we analyzed public documents that were generated over a five-year period. We observed that many public debates were couched within the ES framework and related to management of a range of land cover categories. Our results also indicated the majority of public discussions were descriptive and neutral, with a focus on maintaining the flow of Provisioning, and Regulation and Maintenance services to local communities. Normative tones were adopted, particularly surrounding Cultural ES, despite the limited amount of time that stakeholders dedicated to exploring these topics. Our results reinforce the importance of considering the ES concept as a boundary object that maintains interpretive flexibility and focuses stakeholder attention on points of potential social conflict. The implications that emerge from this research are particularly relevant for protected areas, such as those found in Poland, which are reforming environmental protection plans and seeking communication tools to facilitate public participation, environmental sustainability, and more equitable policy outcomes.
Keywords: ecosystem services; public participation; Natura 2000; land cover; management plans